Atticoantral disease — revisited - Jothiramalingam, S. B. (Springer-Verlag, 2007)
Atticoantral disease is very common in this part of the world. The clinical presentation and the otomicroscopic examination of the ear may just reveal the tip of the iceberg as to the extent of disease. Often we have found that minimal disease with good hearing have extensive mastoid involvement.